2017
DOI: 10.1001/jamapediatrics.2017.1020
|View full text |Cite
|
Sign up to set email alerts
|

Educational Performance of Children Born Prematurely

Abstract: Survivors of preterm birth often present with medical morbidities; however, variation in their long-term educational performance has not been well described.OBJECTIVE To estimate the association between gestational age and 4 outcomes in school-aged children: readiness to enter kindergarten, scores on standardized tests in elementary and middle school, gifted status, and low performance. DESIGN, SETTING, AND PARTICIPANTSIn a retrospective cohort study, children born in Florida between 1992 and 2002 at 23 to 41 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 32 publications
(43 reference statements)
4
30
1
Order By: Relevance
“…While prior studies of preterm children demonstrated that intelligence is negatively associated with GA, 3 , 49 , 78 in our cohort, GA is only an important factor associated with outcome in those without brain injury. In the presence of brain injury and CLD, GA was not independently associated with cognitive outcomes.…”
Section: Discussioncontrasting
confidence: 87%
“…While prior studies of preterm children demonstrated that intelligence is negatively associated with GA, 3 , 49 , 78 in our cohort, GA is only an important factor associated with outcome in those without brain injury. In the presence of brain injury and CLD, GA was not independently associated with cognitive outcomes.…”
Section: Discussioncontrasting
confidence: 87%
“…Future studies are needed—including prospective longitudinal studies and those incorporating a group with known language impairment or structural damage—to further elucidate more beneficial from less beneficial phenotypes, with the aim of developing biomarkers for language network development in EPT. In light of recent evidence that extreme prematurity is not universally devastating for neurological functioning and scholastic performance, investigation into possible markers of resiliency is especially interesting (Garfield et al., ). The reported results comparing high‐functioning TC and EPT with no known brain injury are valuable as a step toward that aim.…”
Section: Discussionmentioning
confidence: 99%
“…Birth weight and its subsequent effect on childhood height and weight may make it difficult to disentangle maturity from ability as larger children may appear to be more mature due to their physical stature. Likewise, gestational age is another avenue one might suspect could affect the age gap (Figlio et al., ; Garfield et al., ). These interactions between initial birth endowments and school starting age have never been studied in the extant literature.…”
Section: Introductionmentioning
confidence: 99%